1986
DOI: 10.2135/cropsci1986.0011183x002600050033x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Salt‐Tolerant and Nontolerant Alfalfa to Salinity during Germination1

Abstract: Identification of the physiological processes involved in salt tolerance is required to develop appropriate selection criteria for breeding salt‐tolerant crops. For this purpose selected physiological characteristics were evaluated in five alfalfa (Medicago sativa L.) populations selected for NaCl tolerance during seed germination and the source population, 'Mesa‐Sirsa'. Seed of the populations (Syn‐1) was germinated in distilled water and solutions of NaCl, NaNO3, KC1, KNO3, and mannitol ranging from −1.0 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…(Table 1). Both the osmotic and toxic effects of the salts have been implicated in the inhibition of the germination (Allen et al, 1986, Machado Neto et al, 2004. Higher germination percentages obtained from NaCl compared to those of PEG at the same concentrations in the same harvest period proved that the adverse effect of PEG on the germination was due to an osmotic effect rather than specific ion accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…(Table 1). Both the osmotic and toxic effects of the salts have been implicated in the inhibition of the germination (Allen et al, 1986, Machado Neto et al, 2004. Higher germination percentages obtained from NaCl compared to those of PEG at the same concentrations in the same harvest period proved that the adverse effect of PEG on the germination was due to an osmotic effect rather than specific ion accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in close conformity with the earlier findings of Alka et al (1981) and Iqbal et al (1998) in which they reported that increasing salinity decreased percent germina on in wheat, barley and triticale. Allen et al (1986) proposed that the reduction in germination percentage under same conditions might be due to the ion toxicity and reduced uptake of water, which affected the physiological and biochemical activities through inhibition of the anabolic or stimulation of catabolic processes (Corchete and Guerra, 1986). As in the germination percentage, there was also a considerable decrease in root and shoot length of both barley varieties with increasing salinity levels of the growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…However, two different mechanisms of salt tolerance enable seeds to germinate at high salt concentrations. Seeds can tolerate the effects of a lower water potential in the substrate (Allen et al 1986) or they may present specific tolerance to the inhibitory effect of NaCl (Rumbaugh et al 1993). In some cases, germination inhibition of Eucaliptus grandis was higher in NaCl than in PEG 6000 solutions at equal osmotic potential (Souza and Cardoso 2000).…”
Section: Introductionmentioning
confidence: 99%